Adeno‐associated virus 9–mediated Cdk5 inhibitory peptide reverses pathologic changes and behavioral deficits in the Alzheimer's disease mouse model. Issue 8 (19th September 2017) - He, Yong; Pan, Suyue; Xu, Miaojing; He, Rongni; Huang, Wei; Song, Pingping; Huang, Jianou; Zhang, Han‐Ting; Hu, Yafang
ABSTRACT: Cyclin‐dependent kinase 5 (Cdk5), which binds to and is activated by p35, phosphorylates multiple substrates and plays an essential role in the development and function of the CNS; however, proteolytic production of p25 from p35 under stress conditions leads to the inappropriate activation of Cdk5 and contributes to hyperphosphorylation of t and other substrates that are related to the pathogenesis of Alzheimer's disease. Selective inhibition of aberrant Cdk5 activity via genetic overexpression of Cdk5 inhibitory peptide (CIP) reduces pathologic changes and prevents brain atrophy and memory loss in p25‐transgenic mice. In the present study, we delivered adeno‐associated virus 9 carrying green fluorescent protein–CIP (AAV9‐GFP‐CIP) to brain cells via intracerebroventricular infusion in amyloid precursor protein/presenilin 1 (APP/PS1) double‐transgenic 3‐mo‐old mice after the occurrence of β‐amyloid (Aβ) aggregation and the hyperphosphorylation of t. Three months of treatment of AAV9‐GFP‐CIP reduced pathologic changes, including t hyperphosphorylation, (Aβ) deposit, astrocytosis, and microgliosis, which were correlated with the reversal of memory loss and anxiety‐like behavior observed in APP/PS1 mice. The neuroprotection effect of AAV9‐GFP‐CIP lasted an additional 7 mo—the end point of the study. These findings provide a novel strategy to selectively target Cdk5 for the treatment of Alzheimer's disease.—He, Y., Pan, S., Xu, M., He, R., Huang, W., Song, P., Huang, J., Zhang, H.‐T., Hu, Y. Adeno‐associated virus 9–mediated Cdk5 inhibitory peptide reverses pathologic changes and behavioral deficits in the Alzheimer's disease mouse model. FASEB J . 31, 3383–3392 (2017). www.fasebj.org